VIRTUAL REALITY IN WOUND CARE: LITERATURE REVIEW - Rabkovskaja, Gražina; Kielė, Viktorija (Slauga. Mokslas ir praktika, 2023)
Burns are a serious problem that causes a lot of discomfort, both for the patient and for the staff, who try to alleviate the pain and anxiety. Virtual reality is an innovative way of separating the patient from the stimulus felt, thus reducing the negative emotions experienced. Study subject – Applying virtual reality to wound care. Objective of the literature review. The aim was to analyse the literature on the use of Virtual Reality (VR) in wound care. Methods. An exploratory literature review to analyse the application of virtual reality in wound care. Results of the literature review. The scientific literature was searched in PubMed. According to the selection criteria, 10 full-text publications relevant to the topic of the study were selected. An exploratory review and analysis of the scientific literature was performed. Conclusions. The use of VR has been shown to be an effective and important adjunct in burn wound care procedures. VR immerses the patient, separating him/her from the painful stimulus, making this distraction an effective way to reduce the pain associated with wound debridement and dressing changes. The most commonly used methods are inclusive and non-inclusive VR. It was also observed that the effect of using VR for wound dressing is positive and that VR itself is an effective way to distract the patient from pain, anxiety and other negative emotions during dressing.